Dog attacks on livestock: insights from Swedish news articles and experiences of farmers and inspectors - Sarenbo, Sirkku; Doane, Marie (Frontiers in Veterinary Science, 2025)
Introduction and purposeWild carnivore predation on Swedish livestock has been meticulously recorded, but dog attacks on livestock tend to be overlooked. This study aimed to map the nature of dog attacks on livestock.Material and methodsData was collected from Swedish news media articles, Rovbase records in the region Västra Götaland, and electronic online surveys of farmers and official inspectors. In addition to descriptive statistics, monthly indices of dog attacks on livestock were calculated using data from Rovbase and news media articles.ResultsHalf of the inspectors had inspected livestock attacked by dogs. Dogs accounted for 3.8% of all predator attacks inspected in Västra Götaland 2004–2024. Most dog attacks occurred during summer and fall. Sheep were most often subjected to dog attack, followed by horses. Sheep were most often attacked by dogs on pastures, hens in their enclosed barnyard, and horses when ridden or driven. The attacking dogs were most often unknown, loose, or unsupervised.DiscussionDog attacks impact both animal welfare and societal interests. The farmers expressed emotional distress after the dog attacks. Misidentification can worsen wolf-related conflicts and misdirect public funds, while livestock owners may face economic losses despite the dog owner’s sole responsibility. Further research is needed to assess dog attacks on livestock nationwide. However, targeted measures such as predator-deterrent fencing, prolonged mandatory leashing of dogs, and enhanced monitoring of grazing livestock during hunting seasons could already be implemented.